Stratification of nitrifier guilds in granular sludge in relation to nitritation. (1st January 2019) - Soler-Jofra, Aina; Wang, Ru; Kleerebezem, Robbert; van Loosdrecht, Mark C.M.; Pérez, Julio
Abstract: A lab-scale partial nitritation granular sludge air-lift reactor was operated in continuous mode treating low strength synthetic medium (influent ca. 50 mg-N-NH4 + /L). Granules were initially stratified with AOB in the external shell and NOB in the inner core at 20 °C. Once temperature was decreased progressively from 20 °C to 15 °C, nitrate production was initially observed during several weeks. However, by maintaining relatively high ammonium concentrations in the liquid (ca. 28 mg-N-NH4 + /L), effluent nitrate concentrations in the reactor decreased in time and process performance was recovered. Batch tests were performed in the reactor at different conditions. To understand the experimental results an existing one-dimensional biofilm model was used to simulate batch tests and theoretically assess the impact of stratification, dissolved oxygen (DO) and short-term effects of temperature on time course concentrations of ammonium, nitrite and nitrate. This theoretical assessment served to develop an experimental methodology for the evaluation of in-situ batch tests in the partial nitritation reactor. These batch tests proved to be a powerful tool to easily monitor the extent of stratification of nitrifier guilds in granular sludge and to determine the required bulk ammonium concentration to minimize nitrite oxidation. When nitrifier guilds were stratified in the granular sludge, a higher bulk ammonium concentration was required to efficiently repress NOB at lower temperature (ca. 19 versus 7 mg-N-NH4 + /L at 15 and 20 °C, respectively). Graphical abstract: Highlights: Stratification of nitrifier guilds can be assessed using batch tests. The tests allow to measure required ammonium concentration for NOB repression. Higher ammonium concentration is needed at lower temperature to repress NOB.